2007
DOI: 10.1111/j.1460-9568.2007.05969.x
|View full text |Cite
|
Sign up to set email alerts
|

Two types of social buffering differentially mitigate conditioned fear responses

Abstract: In a phenomenon known as 'social buffering' in various species, signals from a conspecific animal can mitigate stress responses. This buffering can be achieved either by 'pair-housing' after a stressful event or by 'pair-exposure' to an acute stressor with a conspecific animal. In this study, we compared the impacts of these two types of social buffering on auditory conditioned fear responses in male rats. When subjects were exposed to an auditory conditioned stimulus (CS) that had been paired with foot shocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 24 publications
9
114
1
1
Order By: Relevance
“…Control calls could thus be considered as calls of intermediate arousal, with potentially less vocal buffering effect than expected. In addition, other studies suggested that social buffering is more likely to occur with the physical presence of a conspecific: in rodents, primates and birds, recovery from a stressful event is associated with a close physical proximity between the stressed individual and conspecifics (Fraser & Bugnyar, 2011;Kiyokawa et al, 2007;Levine & Wiener, 1988). As zebra finches exhibit physical affiliative behaviours between mates such as allopreening and clumping, social buffering in this species could require multisensory integration.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Control calls could thus be considered as calls of intermediate arousal, with potentially less vocal buffering effect than expected. In addition, other studies suggested that social buffering is more likely to occur with the physical presence of a conspecific: in rodents, primates and birds, recovery from a stressful event is associated with a close physical proximity between the stressed individual and conspecifics (Fraser & Bugnyar, 2011;Kiyokawa et al, 2007;Levine & Wiener, 1988). As zebra finches exhibit physical affiliative behaviours between mates such as allopreening and clumping, social buffering in this species could require multisensory integration.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Next, SFiA was acquired only following 'training', requiring between 4-5 pairings of the familiar conspecific with the anxiogenic stimuli, suggesting that the social familiarity is acting more like a safety signal than external inhibitor. Finally, expression of SFiA appears to require an active mPFC, whereas social buffering effects in response to the presence of a conspecific at the time of testing appear to be independent of mPFC activation (Kiyokawa et al, 2007(Kiyokawa et al, , 2009.…”
Section: Enhancement Of Sfia With D-cycloserinementioning
confidence: 95%
“…To ensure individual and species survival, complex social behaviors have developed over time (Amodio and Frith, 2006;Cohen, 2004;Strodl and Schausberger, 2012), and in multiple mammalian species, the presence of a conspecific reduces behavioral and autonomic responses to a threat (Davitz and Mason, 1955;DeVries et al, 2003;Hennessy et al, 2000;Hennessy et al, 2002;Kiyokawa et al, 2007Kiyokawa et al, , 2009Kiyokawa et al, , 2012Nakayasu and Kato, 2011;Terranova et al, 1999). Such reductions in threat responses can be even greater when the conspecific is familiar.…”
Section: Introductionmentioning
confidence: 99%
“…In the pair-exposure paradigm, it has been shown that social buffering depends on a partner's stress status, with non-shocked partners being more efficient than shocked partners (Kiyokawa et al 2004b). Moreover, Kiyokawa et al (2007) showed that pair-housing for 24 h with an unfamiliar rat following auditory fear conditioning resulted in a suppressed autonomic response in a fear-conditioned animal. However, they did not observe any differences in freezing response.…”
Section: Discussionmentioning
confidence: 99%